If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + X = -12 Solving -10 + X = -12 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + X = -12 + 10 Combine like terms: -10 + 10 = 0 0 + X = -12 + 10 X = -12 + 10 Combine like terms: -12 + 10 = -2 X = -2 Simplifying X = -2
| 3(4y+7)=33 | | 12=1/9(36x=18) | | 22.5+2(X)=26.75 | | 6(5+7)=6(5)+6(7) | | 6x+6=3(x-4) | | 22.5+2(.75)= | | (X^2+2)-2x^2=0 | | -4=-6+v | | 2x+76y=36 | | 3x-7=2-1+x+7 | | r-5r+4f= | | -4.3-.1(X)=-6.1 | | u-3=-9 | | 5x+85=11x-5 | | -4.3-.1(X)=6.1 | | 5/9x18 | | -4.3-.1(M)=6.1 | | 3y+5=7x | | -4.3-.1(10)= | | 4.5=5.4 | | -4.3-.1(7)= | | 4x+29+12x+55=180 | | -4ln(x)+6ln(x)=ln(27x) | | 3u-17=43 | | 5a(3b+20)= | | (9y+6)-(3y-5)= | | 100r+5=15 | | 5xa+b= | | 28=2x+12 | | 8x+11y=64 | | m/8-6=3 | | 18x+4=0 |